Effects of Anti-Diabetic Drugs on Fracture Risk: A Systematic Review and Network Meta-Analysis - Zhang, Yu-Sheng; Zheng, Yan-Dan; Yuan, Yan; Chen, Shi-Chun; Xie, Bao-Cheng (Frontiers in Endocrinology, 2021)
Purpose Available data on the eﬀects of anti-diabetic drugs on fracture risk are contradictory. Therefore, our study aimed to analyze all available data on the eﬀects of anti-diabetic drugs on fracture risk in type 2 diabetes mellitus (T2DM) patients. Methods Embase, Medline, ClinicalTrials.gov and Cochrane CENTRAL were searched for relevant trials. All data analysis were performed with STATA (12.0) and R language (3.6.0). Risk ratio (RR) with its 95% confidence interval (CI) was calculated by combining data for the fracture effects of anti-diabetic drugs, including SGLT2 inhibitors, DPP-4 inhibitors, GLP-1 receptor agonists, meglitinides, α-glucosidase inhibitors, thiazolidinediones, biguanides, insulin and sulfonylureas. Results 117 eligible randomized controlled trials (RCTs) with 221,364 participants were included in this study. Compared with placebo, trelagliptin (RR 3.51; 1.58-13.70) increased the risk of fracture, whereas albiglutide (RR 0.29; 0.04-0.93) and voglibose (RR 0.03; 0-0.11) decreased the risk of fracture. Other medications were comparable in terms of their effects on fracture risk and no statistically significance was observed. In terms of fractures, voglibose (0.01%) may be the safest option and trelagliptin (13.64%) may be the worst. Sensitivity analysis results were consistent with those of the main analysis. No statistically significant differences were observed in the regression coefficients of age (1.03; 0.32-2.1), Follow-up duration (0.79; 0.27-1.64) and sex distribution (0.63; 0.15-1.56). Conclusions We found varied results on the association between the use of anti-diabetic drugs and fracture risk. Specifically, trelagliptin raised the risk of fracture, whereas voglibose and albiglutide showed benefit with statistical difference. Other drugs were comparable in terms of their effects on fracture risk. Some drugs (omarigliptin, sitagliptin, vildagliptin, saxagliptin, empagliflozin, ertugliflozin, rosiglitazone, pioglitazone, and nateglinide) may increase the risk of fracture, while other ones (such as dulaglutide, exenatide, liraglutide, semaglutide, lixisenatide, linagliptin, alogliptin, canagliflozin, dapagliflozin, glipizide, gliclazide, glibenclamide, glimepiride, metformin, and insulin) may show benefits. The risk of fracture was independent of age, sex distribution and the duration of exposure to anti-diabetic drugs. When developing individualized treatment strategies, the clinical efficacy of anti-diabetic drugs must be weighed against their benefits and risks brought about by individual differences of patients.